Minimum Divergence Estimators, Maximum Likelihood and the Generalized Bootstrap - Michel Broniatowski (Entropy, 2021)
This paper states that most commonly used minimum divergence estimators are MLEs for suited generalized bootstrapped sampling schemes. Optimality in the sense of Bahadur for associated tests of fit under such sampling is considered.